A theoretical and experimental approach to the adiabaticity of diffusional electron transfer processes. Electroreduction of 2-nitropropane on mercury microelectroelectrodes - Laborda, E; Suwatchara, D; Batchelor-McAuley, C; Compton, R (2013)
A theoretical and experimental approach to the degree of adiabaticity of electrode processes is considered for the case where the electroactive species of the redox couple move freely in solution. Within a transition state-like framework, the adiabatic effect on the activation energy of electron transfer is included through the theory developed by Schmickler (W. Schmickler, J. Electroanal. Chem. 204 (1986) 31). The effect on the probability of electron tunnelling is also incorporated according to the Landau-Zener formalism (L. Landau, Phys. Z. Sowjetunion, 1932 [29]; C. Zener, Proc. R. Soc. London A 140 (1933) 660). In applying both aspects, it is recognised that the electron transfer takes place over a range of distances from the electrode surface. The theory is applied to the study of the electroreduction kinetics of 2-nitropropane in fully-supported DMSO solutions on mercury hemispherical microelectrodes of 23 μm radius. By fitting of experimental cyclic voltammetry, the standard rate constant (k0) is determined at different temperatures and for different supporting electrolytes. The reorganization energy and degree of adiabaticity from the variation of k 0 with temperature are evaluated. © 2013 Elsevier B.V. All rights reserved.